1996
DOI: 10.1063/1.471281
|View full text |Cite
|
Sign up to set email alerts
|

Quantum scattering calculations on the NH3+OH→NH2+H2O reaction

Abstract: Articles you may be interested inQuasiclassical trajectory calculations for the OH(X 2Π) and OD(X 2Π)+HBr reactions: Energy partitioning and rate constantsThe product vibrational, rotational, and translational energy distribution for the reaction O(3 P J )+O3→2O2: Breakdown of the spectator bond mechanism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 72 publications
0
34
0
Order By: Relevance
“…To gain a deeper knowledge of the behaviour of the excitation function, we also performed QCT calculations on the PES-1996 11 classical analysis we found that the excitation function also presents a peak at low energies (although less pronounced), which seems to indicate that it is due to the nature of the PES rather than to quantized states. Therefore, whether this peak is a real feature or a consequence of the reduced-dimensional model and/or the PES used is an open question, which deserves more theoretical and/or experimental analysis.…”
Section: Excitation Functionmentioning
confidence: 97%
See 4 more Smart Citations
“…To gain a deeper knowledge of the behaviour of the excitation function, we also performed QCT calculations on the PES-1996 11 classical analysis we found that the excitation function also presents a peak at low energies (although less pronounced), which seems to indicate that it is due to the nature of the PES rather than to quantized states. Therefore, whether this peak is a real feature or a consequence of the reduced-dimensional model and/or the PES used is an open question, which deserves more theoretical and/or experimental analysis.…”
Section: Excitation Functionmentioning
confidence: 97%
“…11 Thus, when the reduced-dimensional QM calculations are compared with QCT results (obtained in the present paper) on the same PES-1996 surface, the approximations included in the methods are analyzed, and when the QCT results are compared on different surfaces, PES-1996 and PES-2012, the PES is analyzed.…”
Section: B Quasi-classical Trajectory Calculationsmentioning
confidence: 99%
See 3 more Smart Citations